Acrylonitrile butadiene styrene (ABS) and polycarbonate (PC) filaments three-dimensional (3-D) printer emissions-induced cell toxicity. (15th December 2019) - Farcas, Mariana T.; Stefaniak, Aleksandr B.; Knepp, Alycia K.; Bowers, Lauren; Mandler, William K.; Kashon, Michael; Jackson, Stephen R.; Stueckle, Todd A.; Sisler, Jenifer D.; Friend, Sherri A.; Qi, Chaolong; Hammond, Duane R.; et al.
Graphical abstract: Highlights: Fused filament fabrication 3-D printer emissions consist of particles and organic compounds. PC filament 3-D printer generated more particles than ABS at an equivalent printing time. Both PC and ABS 3-D printer emissions induced cell toxicity in human small airway epithelial cells. Abstract: During extrusion of some polymers, fused filament fabrication (FFF) 3-D printers emit billions of particles per minute and numerous organic compounds. The scope of this study was to evaluate FFF 3-D printer emission-induced toxicity in human small airway epithelial cells (SAEC). Emissions were generated from a commercially available 3-D printer inside a chamber, while operating for 1.5 h with acrylonitrile butadiene styrene (ABS) or polycarbonate (PC) filaments, and collected in cell culture medium. Characterization of the culture medium revealed that repeat print runs with an identical filament yield various amounts of particles and organic compounds. Mean particle sizes in cell culture medium were 201 ± 18 nm and 202 ± 8 nm for PC and ABS, respectively. At 24 h post-exposure, both PC and ABS emissions induced a dose dependent significant cytotoxicity, oxidative stress, apoptosis, necrosis, and production of pro-inflammatory cytokines and chemokines in SAEC. Though the emissions may not completely represent all possible exposure scenarios, this study indicate that the FFF could induce toxicological effects. Further studies are needed to quantify the detected chemicals in the emissions and their corresponding toxicological effects.